Upskilling Kompetensi Profesional Pendidik Vokasi melalui Pelatihan Kendali Motor Listrik berbasis Variable Speed Drive - Yanto, Doni Tri Putra; Muslim, Muslim; Dewi, Citra; Aswardi, Aswardi; Zaswita, Hermi (Jurnal Pendidikan Teknik Elektro, 2024)
Sekolah Menengah Kejuruan Negeri (SMKN) 2 Payakumbuh is one of the vocational high schools that offers various areas of expertise, one of which is Electrical Power Installation. This program aims to produce graduates who are ready to work and competent in the field of electrical power installation. SMKN 2 Payakumbuh is committed to conducting quality and optimal learning processes to achieve its goal of producing graduates who are well-prepared and skilled in their fields. However, there are some challenges in the learning process within the Electrical Power Installation expertise, particularly in the subject of Motor Installation. According to the latest curriculum, new material has been added to the motor installation subject, specifically motor control using a speed drive device. However, the school lacks sufficient laboratory equipment to support this practical material. Additionally, the teachers' competence in motor control using Variable Speed Drive (VSD) devices is still limited, which hinders the learning process from being fully effective. Several actions were taken to address this issue, including creating a motor control trainer based on VSD and conducting training to enhance teachers' competencies in motor control using VSD. This initiative was carried out in four stages: (1) Planning; (2) Preparation; (3) Implementation; and (4) Evaluation and reporting. As a result of these efforts, the teachers' competence in motor control using VSD has improved.